2012
DOI: 10.1186/1472-6882-12-67
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of radix dipsaci, pyrola herb, and cynomorium songaricum on bone metabolism of ovariectomized rats

Abstract: BackgroundThe objective of this study was to evaluate the effects of herbal medicines, such as Radix Dipsaci (RDD), Pyrola Herb (PHD), and Cynomorium songaricum decoction (CSD), on osteoporotic rats induced by ovariectomy (OVX).MethodsOVX or sham operations were performed on 69 virgin Wistar rats that were divided into six groups: sham (sham, n = 12), OVX control group (OVX, n = 12), and OVX rats with treatments (diethylstilbestrol, E2, n = 12; RDD, n = 11, PHD, n = 11, and CSD, n = 11). Non-surgical rats serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 15 publications
(17 reference statements)
1
19
0
Order By: Relevance
“…the exact mechanism underlying is still unknown. Our previous study and others showed that Radix Dipsaci decoction and Pyrola Herb decoction enhanced significantly bone formation in OVX rats [8,14]. Our results in this study showed that Chinese herbs SACD and RCD increased bone formation by stimulating OPG expression and downregulating RANKL expression in OB and bMSC.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…the exact mechanism underlying is still unknown. Our previous study and others showed that Radix Dipsaci decoction and Pyrola Herb decoction enhanced significantly bone formation in OVX rats [8,14]. Our results in this study showed that Chinese herbs SACD and RCD increased bone formation by stimulating OPG expression and downregulating RANKL expression in OB and bMSC.…”
Section: Discussionsupporting
confidence: 65%
“…However, the anti-osteoporotic mechanisms are still unknown. Our previous studies suggest that Chinese herbs increased bone formation by stimulating OPG expression and downregulating RANKL in bone marrow cells [8]. The anti-osteoporotic effects are selective for these herbs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results found that most CHM coprescribed with AIs was used for arthritis and pain relief. For example, du-huo-ji-sheng-tang and xu-duan ( Dipsaci radix ) are used to treat osteoarthritis, osteoporosis, and other bone diseases 3841. Shao-yao-gan-cao-tang is used to relieve dysmenorrhea and muscle pain 42…”
Section: Discussionmentioning
confidence: 99%
“…Following multiple washes in 4X SSC at room temperature, the slides were incubated at 37˚C in a blocking reagent for 30 min, a biotinylated anti-digoxin antibody for 60 min, SABC for 20 min and the biotinylated peroxydase for 20 min, at 37˚C, followed by staining with DAB (Sigma, St. Louis, MO, USA). Sections were then covered with glycerol-gelatin and coverslips for microscopic examination (11,12). The SATB1 probe (sequence: 5'-TCTTTAATTTCTAATATATTTAGAA-3') was synthesized and labeled with biotin at the 5' end by Sangon Bioengineering Technology and Services Co., Ltd. (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%